Field evaluation of the establishment potential of wmelpop Wolbachia in Australia and Vietnam for dengue control - Simmons, Cameron (2018)
BACKGROUND: Introduced Wolbachia bacteria can influence the susceptibility of Aedes aegypti mosquitoes to arboviral infections as well as having detrimental effects on host fitness. Previous field trials demonstrated that the wMel strain of Wolbachia effectively and durably invades Ae. aegypti populations. Here we report on trials of a second strain, wMelPop-PGYP Wolbachia, in field sites in northern Australia (Machans Beach and Babinda) and central Vietnam (Tri Nguyen, Hon Mieu Island), each with contrasting natural Ae. aegypti densities. METHODS: Mosquitoes were released at the adult or pupal stages for different lengths of time at the sites depending on changes in Wolbachia frequency as assessed through PCR assays of material collected through Biogents-Sentinel (BG-S) traps and ovitraps. Adult numbers were also monitored through BG-S traps. Changes in Wolbachia frequency were compared across hamlets or house blocks. RESULTS: Releases of adult wMelPop-Ae. aegypti resulted in the transient invasion of wMelPop in all three field sites. Invasion at the Australian sites was heterogeneous, reflecting a slower rate of invasion in locations where background mosquito numbers were high. In contrast, invasion across Tri Nguyen was relatively uniform. After cessation of releases, the frequency of wMelPop declined in all sites, most rapidly in Babinda and Tri Nguyen. Within Machans Beach the rate of decrease varied among areas, and wMelPop was detected for several months in an area with a relatively low mosquito density. CONCLUSIONS: These findings highlight challenges associated with releasing Wolbachia-Ae. aegypti combinations with low fitness, albeit strong virus interference properties, as a means of sustainable control of dengue virus transmission.